Toward complementarity: Specificity and commonality in social‐emotional development: Introduction to the special section. Issue 6 (17th October 2021) - Malti, Tina; Cheah, Charissa S. L.; ,
Abstract: What are the roles of specificity and commonality in social‐emotional development? We begin by highlighting the conceptual context for this timely and timeless question and explain how responses to it can inform novel lines of theoretical and empirical inquiry, as well as sociocultural generalizability. Next, we describe how the selection of papers included in this special section contributes to our understanding of specificity and commonality in social‐emotional development. We then explain how applying the complementarity principle to social‐emotional development can inform a future research agenda in this domain. Lastly, we discuss how specificity and commonality fundamentally impact the way we conceptualize and implement interventions aimed at nurturing social‐emotional development in every child.